Representasi Makna Pesan Harapan pada Iklan Grab di Media Sosial Youtube - Dede Lilis Chaerowati; Resti Rahmawati Dewi (UNISBA Press, 2023)
Abstract. In this study, the author discusses the representation of an advertisement on YouTube social media, namely from the Grab advertisement in 2021 with the